Agama dan Pro-Kontra Gerakan Dakwah Radikal di Indonesia - Miftakun Niam; Muhammad Bimo Ginantoko; Sahrul Ramadhani; Wahyu Pratiwi; Tafsir Tafsir; Ismail Ismail; Ahmad Fauzan Hidayatullah (JIA (Jurnal Ilmu Agama), 2022)
Radicalism does not only revolve around religious ideology, but has also been incarnated in social, political and cultural life. That is, any ideology or thought that has a negative impact (effect) causes a person to become militant and fanaticism can be included in radicalism. Religious radicalism has recently emerged, inviting someone to adapt to other people. This concerns the practice of life (mu'amalah) and worship (ubudiyah), especially regarding the different views on their religion. Different interpretations see that religious law is exacerbated by selfish reasons that lead to the breakdown of harmony in society. What is considered not in accordance with the same understanding, is considered to deviate from the true teachings of Islam. Later, many influential people asked the person to return to the true religious teachings. He views hat religious teachings must deviate from the practice of life. Unfortunately, this true teaching is only based on their own understanding. For him, the teachings he received were considered pure and represented the true and legitimate teachings of Islam. If things like this continue, then surely the internal division of religious communities will be wide open and it turns out that the mass organization movement that smells of radicalism in the name of religion does not only happen to Islam, but also to others. religion.